RESEARCH IN THE FIELD OF TRANSLATION AS A COMPONENT OF THE PROCESS OF FORMING THE RESEARCH COMPETENCE OF FUTURE TRANSLATORS - Derbak Olha; Vasyliuk Valeriia (Вісник Університету імені Альфреда Нобеля. Серія Педагогіка і психология)
The article attempts to reveal the problem of research in the field of translation as a component of the process of forming the research competence of future translators. The aim of the article is to study the peculiarities of translation studies and their role in the development of future translators’ research competence. The relevance of the study is substantiated, which is determined by the fact that the profession of translator is currently one of the most prestigious and popular professions in the world; there is the demand for new types of translators – fixer translators and military translators, which is due to the beginning of Russia’s full-scale invasion of Ukraine. It is noted that the subject of translation studies is the study of the regularities of the translation process and the factors that affect the course of the translation process and determine the result of the translation. The features of the areas of research in the field of translation are considered. It is established that foreign scholars distinguish the following areas of research in translation studies: text analysis and translation; translation quality assessment; genre translation; multimedia translation; translation and technology; history of translation; translation ethics; terminology and glossaries; interpretation; translation process; training of translators; and the profession of translator. It is noted that translators have the opportunity to conduct their research in several fields with different directions and orientations. Some translators choose one of the areas of comparative research, while other translators use different types of questionnaires and interviews to measure the relationship or importance of a specific translation-related issue. Another important area of research in the field of translation is considered – research in the field of training future translators, since conducting high-level translation research requires a translator to have developed research competence. It has been proved that a higher education institution should train a specialist researcher who tries to disseminate and explore new methods of work, who should form new ideas and is able to put them into practice. The future specialist should develop the skills of independent creative scientific work, form a circle of their scientific interests, master the norms and scientific and methodological principles of experimental and research activities. The basis of the research competence of future translators is the ability to identify the problem in time, formulate a hypothesis, select and analyse the necessary information for the study, select the necessary methods of research and data processing, focus not only on the final but also on intermediate results of the study, discuss the possibility of interpreting the results of the study, and use the results of the study in practical activities. These characteristics determine the ability of future translators to conduct scientific research in the field of topical issues of modern humanities, linguistics, literary studies, translation studies and are an important indicator of the high qualification of these specialists. The study organizes and systematizes the available knowledge on the problem of the essence and directions of translation studies, allowing, after appropriate adaptation, applying it in the process of forming the research competence of future translators. The prospects for further research on this issue include the development of pedagogical conditions for the formation of future translators’ research competence, taking into account the peculiarities and directions of translation studies.